Mechanism and optimization of hydrocyclone-based enrichment of calcium and magnesium in fine coal gangue - Zhicheng Liu; Hao Pan; Tianqi Song; Zhiwei He (PLoS ONE, 2026)
Coal gangue, an industrial solid waste generated during coal mining and processing, poses significant environmental challenges due to long-term stockpiling and landfilling. Its comprehensive utilization requires not only decarbonization but also the enrichment of valuable components such as calcium and magnesium through hydrocyclone separation. In this study, the multicomponent occurrence characteristics of coal gangue were examined at the microscale, and the flow-field behavior of hydrocyclones was investigated using computational fluid dynamics (CFD). Based on these insights, a hydrocyclone enrichment system for calcium and magnesium was developed by optimizing cyclone structure and operational parameters. The raw coal gangue exhibited a high ash content (81.66%), mainly composed of Al and Si, with 2.39% Ca and 0.46% Mg. After crushing to 0–1 mm, Ca was enriched in coarse, high-density fractions, while Mg was concentrated in fine, high-density fractions. In the conventional hydrocyclone, increasing feed velocity improved pressure and tangential velocity but caused instability in the locus of zero vertical velocity (LZVV) and air-core morphology, limiting separation accuracy. The bottom-impact hydrocyclone demonstrated superior performance at an impact-tube height of 80 mm and an impact velocity of 5 m/s, achieving improved pressure distribution, higher tangential velocity, and more stable air-core symmetry. Compared with the conventional design, the optimized structure enhanced classification efficiency from 92.47% to 96.13% and increased the Ca content in the underflow to 3.53%. However, Mg separation remained limited under all tested conditions.